1971
DOI: 10.3758/bf03337887
|View full text |Cite
|
Sign up to set email alerts
|

Short-term sequential memory for pictures and words

Abstract: Pictures, concrete nouns, or abstract nouns were presented sequentially at rates of 5.3 or 2 items/sec, the faster rate being designed to prevent implicit labeling of pictures during input while permitting pictures to be recognized and words to be read. Sequential mel'Qory was tested by means of aserial reconstruction task. Consistent with previous findings for immediate memory span, sequential memory was better for words than for pictures at the fast but not at the slower rate. The results further Sttpport a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 2 publications
1
24
0
Order By: Relevance
“…Paivio et al (1968) suggest a reason for this superiority with the hypothesis that while textual material is stored in propositional format only, images are stored both in visual and in propositional format, and may therefore have the advantage of dual coding. Similarly, Paivio (1971a) showed that concrete words are memorised better than abstract words, and that, among concrete words, those which most easily conjure up images are retained the best. He postulates that there are two functionally distinct subsystems of interconnected coding.…”
Section: Multimodal Presentation and Information Processingmentioning
confidence: 96%
“…Paivio et al (1968) suggest a reason for this superiority with the hypothesis that while textual material is stored in propositional format only, images are stored both in visual and in propositional format, and may therefore have the advantage of dual coding. Similarly, Paivio (1971a) showed that concrete words are memorised better than abstract words, and that, among concrete words, those which most easily conjure up images are retained the best. He postulates that there are two functionally distinct subsystems of interconnected coding.…”
Section: Multimodal Presentation and Information Processingmentioning
confidence: 96%
“…Regarding memory-encoding strategies, the mental-image strategy is cognitively more demanding because, unlike the rehearsal strategy, it requires the creation of a link between the word and the corresponding visual representation in memory (Craik & Tulving, 1975;Froger, et al, 2012;Froger, Toczé, & Taconnat, 2014;Paivio & Csapo, 1971;Toczé, Bouazzaoui, & Taconnat, 2012;Tournier & Postal, 2011). The success of its execution will thus be tightly linked to the availability of cognitive resources.…”
mentioning
confidence: 95%
“…Indeed, the mental-image strategy requires the largest amount of executive resources (Craik & Tulving, 1975;Paivio & Csapo, 1971;Plaie & Thomas, 2008), especially in older adults (Froger et al, 2012;Tournier & Postal, 2011). This strategy requires the retrieval of information (a corresponding image) from long-term memory.…”
mentioning
confidence: 99%
“…In general, elaborative encoding tasks, such as imaging (Paivio & Csapo, 1973) or categorizing the item into superordinate categories (Smith & Magee, 1980), eliminate or reverse superior memory for pictures. Other encoding manipulations that have eliminated or reversed the effect include paired-associate learning with schematically similar pictures (Nelson, Reed, & Walling, 1976) and serial learning at very rapid presentation rates (Nelson, Reed, & McEvoy, 1977;Paivio & Csapo, 1971). Although the picture superiority effect can be eliminated or reversed by manipulating encoding demands, it has proven relatively insensitive to changes in retrieval demands.…”
mentioning
confidence: 99%